Some Properties of M-Accretive Operators in Normed Spaces - Sari, Christina Kartika (Universitas Muhammadiyah Surakarta, 2015)
Multivalued mapping in normed space has been extensively studied in Mathematical analysis. One example of multivalued mapping is normalized duality mapping. This mapping leads us to another example of multivalued operator, named accretive operator, which is also a multivalued operator. This study was aimed to examine the basic concepts of accretive and maccretive operator. Furthermore, discussion on some properties of accretive and m-accretive operator was provided.